2004
DOI: 10.1016/j.otohns.2004.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Surface Electromyographic Studies of Swallowing in Normal Subjects: A Review of 440 Adults. Report 3. Qualitative Data

Abstract: The normal muscle activity during swallows and drinking has several graphic patterns which can be identified and described similar to EKG records when surface EMG is rectified and filtered. The method of EMG recording is quick and simple, and can be used for screening and evaluation purposes in outpatient and inpatient ENT departments. These parameters represent activities required for normal deglutition, and can be used to identify abnormalities in ENT patients, and provide a basis for comparison of swallowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
84
1
30

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(127 citation statements)
references
References 10 publications
12
84
1
30
Order By: Relevance
“…Kleim and Jones (2008) found no age effects in submental muscle activity during various swallowing tasks consisting on different textures and tastes of liquids and solids. However, Vaiman et al (2004) found a non-significant trend toward a decrease in submental activity during swallowing with age, which supports the current results. Age-related changes in muscle properties, known as sarcopenia (Evans 1995), can affect MEP and sEMG magnitude, since they are recorded from peripheral muscles.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Kleim and Jones (2008) found no age effects in submental muscle activity during various swallowing tasks consisting on different textures and tastes of liquids and solids. However, Vaiman et al (2004) found a non-significant trend toward a decrease in submental activity during swallowing with age, which supports the current results. Age-related changes in muscle properties, known as sarcopenia (Evans 1995), can affect MEP and sEMG magnitude, since they are recorded from peripheral muscles.…”
Section: Discussionsupporting
confidence: 89%
“…Another study measured MEPs from the upper limb and found no gender effects on MEP magnitude and latency in younger subjects, after correcting the latencies for the subject's arm length (Livingston et al 2010). Previous research also found no gender effects on non-stimulated submental sEMG amplitude during swallowing (Vaiman et al 2004).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…It highlights the repetition of a movement or a function of a muscle or muscle group 4,10,11,13,18,20,26,29,[40][41][42][43][44][45][46][47] .…”
Section: -2 -Electromyographymentioning
confidence: 99%
“…Vaiman et al, (2004a, b) analisaram a deglutição de volume livre de água, volume excessivo de água e de 100mL de agua. Foram consideradas as seguintes variáveis: duração da deglutição de saliva e 100mL, número e mL por deglutição em 100mL (Vaiman et al, 2004a), pico de atividade de masseter e temporal na deglutição de saliva (Vaiman et al, 2004b). Nesta amostra, foi verificado que a duração média da deglutição de saliva para indivíduos com menos de 70 anos foi de 3,22 segundos, considerando as fases oral e faríngea, e a deglutição de 100mL para a mesma faixa etária durou de 10,9±2,3 a 13,4±4,0.…”
Section: )unclassified